1987
DOI: 10.1128/aem.53.9.2077-2081.1987
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of animal viruses during sewage sludge treatment

Abstract: Using a previously developed filter adsorption technique, the inactivation of a human rotavirus, a coxsackievirus B5, and a bovine parvovirus was monitored during sludge treatment processes. During conventional anaerobic mesophilic digestion at 35 to 36°C, only minor inactivation of all three viruses occurred. The k' values measured were 0.314 log10 unit/day for rotavirus, 0.475 lglo unit/day for coxsackievirus B5, and 0.944 log10 unit/day for parvovirus. However, anaerobic thermophilic digestion at 54 to 56°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…While our data as well as those of other studies (34,79) thus showed a reduction in the heterogeneity among viruses under extreme conditions, other works have demonstrated that some heterogeneity in virus inactivation kinetics is conserved even under high-pH and -temperature conditions (29,57,63,80,81). Very resistant viruses include phage (82) and ⌽X174 (this study) for high pH and parvovirus and Salmonella phage 28B for high temperature (30,(83)(84)(85)(86). The reasons for these resistant behaviors remain unknown.…”
Section: Discussionsupporting
confidence: 71%
“…While our data as well as those of other studies (34,79) thus showed a reduction in the heterogeneity among viruses under extreme conditions, other works have demonstrated that some heterogeneity in virus inactivation kinetics is conserved even under high-pH and -temperature conditions (29,57,63,80,81). Very resistant viruses include phage (82) and ⌽X174 (this study) for high pH and parvovirus and Salmonella phage 28B for high temperature (30,(83)(84)(85)(86). The reasons for these resistant behaviors remain unknown.…”
Section: Discussionsupporting
confidence: 71%
“…Although more experimentation is needed, it seems that bacteriophages may be potential model organisms for determining the fate of human viruses in different kinds of sludges, as in the different types of sludges studied, they seem to behave like viruses. Bacteriophages inactivate differently according to the various treatment conditions, as has been described for human viruses (Kock and Strauch 1981;Spillman et al 1987;Straub et al 1994). Therefore, the use of more resistant phages is likely to be recommended.…”
Section: ----mentioning
confidence: 95%
“…The microbiological requirements can be achieved by various means, notably by pasteurization of the raw sewage sludge followed by mesophilic anaerobic fermentation. Besides inactivating bacteria and parasitic ova, these processes were shown to inactivate enteric viruses of concern for humans (28,31).…”
mentioning
confidence: 99%
“…In the present study, we adopted a previously described filter sandwich technique (28,31) to determine the in situ inactivation kinetics of several viruses in various animal excreta that were stored under nonaerated conditions. The results show that, at ambient temperature, some viruses withstand inactivation for extended periods.…”
mentioning
confidence: 99%